Hubungan Dukungan Sosial Keluarga Dan Strategi Koping Dengan Kesehatan Mental Narapidana Di Lembaga Pemasyarakatan Kelas IIA Purwokerto - Gigih Fajar Anzani; Rakhmat Susilo (Jurnal Keperawatan Muhammadiyah, 2020)
Mental health is a problem that always attracts attention of public. Mental health is the problem that never escapes and is always being a public concern. Mental insecurity can be experienced by all people including prisoners, especially prisoners who live in residential rooms for quite a long time. It can be several years, decades or even a lifetime. To figure out the relationship between family social support, coupling strategies, and prisoners' mental health in Penitentiary of Class IIA in Purwokerto. The study used descriptive correlational with cross sectional approach. The samples were collected by using random sampling technique. There were 89 respondents who fit the inclusion and exclusion criteria. The type of questionnaire used in this study was a closed questionnaire because the alternative answers have been provided by researchers and the respondents could immediately put a checkmark () in the column provided. There was the relationship between family social support and the prisoners' mental health with p value = 0.000. There was the relationship between coupling strategy and the prisoners mental health with p value = 0.003. There is the positive and meaningful relationship among family social support, coupling strategy, and the prisoners mental health in Penitentiary of Class IIA in Purwokerto.Keywords: health, mental, support, social, family, coupling, prisoners